Preparation method of high-flux efficient catalytic ceramic membrane
The high-throughput and high-efficiency catalytic ceramic membrane prepared by in-situ sintering method solves the problems of low catalyst efficiency and difficulty in separation in the prior art, realizes efficient degradation of organic pollutants and catalyst stability, and improves the efficiency and sustainability of water treatment.
Patent Information
- Application Number
- CN202411837356.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-13
AI Technical Summary
In the prior art, when treating organic pollutants, the catalyst is inefficient and difficult to quickly separate, resulting in low process efficiency after separation from water treated.
In situ sintering method is used to mix Prussian-like blue with alumina in proportion, and a ceramic membrane is prepared by dry press molding and sintering at high temperature to form a high-throughput and high-efficiency catalytic ceramic membrane with a porous structure and uniformly distributed catalytic active sites.
It improves catalytic efficiency, extends the service life of the membrane, reduces the sintering temperature of alumina, reduces the process cost, and achieves high-throughput and efficient in-situ degradation of organic pollutants.
Smart Images

Figure CN119701654A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of functional ceramic membrane preparation, and specifically relates to a method for preparing a high-throughput and high-efficiency catalytic ceramic membrane for in-situ degradation of organic pollutants. The method combines ceramic membrane filtration with AOP technology to achieve high-throughput and high-efficiency in-situ degradation of organic pollutants on the membrane surface. Background Art
[0002] According to the 2023 United Nations World Water Development Report, 3.6 billion people in the world lack safe drinking water, 44% of domestic sewage is not effectively treated, and 1.4 million people died from water pollution in 2019. Improper management of some refractory organic matter (including textile wastewater, dye wastewater, and medical wastewater) means that the water environment associated with hundreds of millions of people may be dangerously polluted or chemically contaminated. Naturally occurring chemicals, especially in groundwater, may also have significant health effects, including arsenic and fluoride, while the levels of other chemicals (such as lead) in drinking water may increase due to leaching from water supply components that come into contact with drinking water. Drinking water contaminated by microorganisms can spread diseases such as diarrhea, cholera, dysentery, typhoid and polio, resulting in approximately 500,000 deaths from diarrhea each year.
[0003] In recent years, the deep water pollution treatment technology based on peroxymonosulfate (PMS) activation and oxidation of organic pollutants has attracted much attention. Traditional PMS activation methods mainly include using transition metal ions, metal oxides, UV, ultrasound and other methods to break the peroxy bonds of PMS to produce sulfate radicals (SO4• − ) and hydroxyl radicals (HO•), thereby achieving the degradation and mineralization of organic pollutants. The energy consumption of activated PMS technology is highly correlated with the dosage of oxidants and catalysts. The catalytic efficiency of metal catalysts is low, and metal catalysts and metal oxides need to be separated from the treated water. These factors will have a significant impact on the process efficiency. Therefore, it is urgent to develop efficient catalysts to achieve efficient sewage treatment, degrade organic pollutants, and quickly separate the treated water from the catalyst.
[0004] Ceramic membrane is a solid membrane material in membrane separation technology. It has been rapidly developed in the past half century due to its advantages of high temperature resistance and chemical corrosion resistance, insensitivity to biological erosion, lower maintenance cost, high mechanical strength, long service life, and easy assembly of flat modules. It has been widely used in petrochemical, pharmaceutical, electronic, metallurgical, food and environmental protection fields. Ceramic membrane is corrosion-resistant and easy to separate from the treated water phase. Furthermore, the surface of the ceramic membrane has a porous structure and can be used as a good catalyst attachment carrier. In the past, the catalyst was often attached to the membrane surface by the impregnation loading method, but it has the disadvantages of unstable catalyst loading and easy to be washed away from the membrane surface by hydraulic force or some macromolecular substances during sewage treatment. The in-situ sintering method has a stable structure. After sintering, the catalyst is distributed on the surface and inside of the membrane. Compared with the membrane loaded with catalyst by the impregnation method, the catalyst of the in-situ sintered membrane is not easy to lose and has a relatively longer service life. Attaching PMS to the ceramic membrane for activation catalysis can not only effectively improve the efficiency of the catalytic process, but also promote the sustainable development of water treatment technology. This combination of technologies is expected to play an important role in solving current problems in the degradation of organic pollutants and provide new solutions for the efficient use and sustainable development of global water resources. Summary of the invention
[0005] In order to solve the above problems, the present invention aims to provide a method for preparing a high-throughput and high-efficiency catalytic ceramic membrane. The prepared ceramic membrane can achieve high-throughput and high-efficiency in-situ degradation of organic pollutants.
[0006] The technical solution adopted by the present invention is as follows: A method for preparing a high-throughput and high-efficiency catalytic ceramic membrane comprises the following steps: (1) Prussian blue (PBA) and Al2O3 are mixed uniformly in proportion by ball milling, wherein the particle size of PBA and Al2O3 is 100-200 nm. Subsequently, a mold with a diameter of 30 mm and a hydraulic press are used to press the mixture at a pressure of 10-30 kPa for 3-7 minutes to obtain a dry blank of the membrane with a thickness ranging from 2-4 mm.
[0007] (2) The alloy is then sintered in an air atmosphere at a high temperature for 5.5 to 6.5 hours using a muffle furnace, with a heating rate of 5°C per minute.
[0008] As one of the preferred technical schemes for the preparation method of the above-mentioned high-throughput and high-efficiency catalytic ceramic membrane, the Prussian blue-like material is prepared by the following method: 1.20-3.00 g of potassium ferrocyanide powder and 1.5-2.5 g of cobalt chloride powder are dissolved in 50-200 ml of water at 25°C, stirred continuously for 24 hours, and centrifuged and dried to obtain a Prussian blue-like material (PBA).
[0009] As one of the preferred technical solutions for the preparation method of the above-mentioned high-throughput and high-efficiency catalytic ceramic membrane, the mass ratio of PBA to Al2O3 is 1:3~5, preferably 1:4~5, and more preferably 1:4.
[0010] As one of the preferred technical solutions for the preparation method of the above-mentioned high-flux and high-efficiency catalytic ceramic membrane, the temperature of the high-temperature sintering is 950~1100°C, preferably 950~1000°C, and more preferably 950°C.
[0011] The present invention also provides a ceramic membrane prepared by the above method. After preparing the catalytic ceramic membrane, the water permeability of the prepared ceramic membrane is tested through a membrane filtration reactor; the prepared membrane is used to activate peroxymonosulfate in an edible brilliant blue solution, and the catalytic performance of the membrane is tested to characterize the good performance of the membrane, so as to achieve a good combination of ceramic membrane-PMS technology for high-throughput and high-efficiency in-situ degradation of organic pollutants in water.
[0012] Therefore, the high-flux and high-efficiency catalytic ceramic membrane prepared by the present invention can be used in the field of water treatment.
[0013] The present invention adopts an in-situ sintering method to dope the catalytic material into the ceramic support to obtain an integrated high-throughput and high-efficiency catalytic ceramic membrane. Compared with the prior art, the present invention has the following outstanding features and outstanding progress: 1. Prussian blue is added to the prepared catalytic ceramic membrane, and after firing, the membrane has a good porous structure and the active sites of the catalyst are evenly distributed on the membrane surface and in the membrane pores.
[0014] 2. During the sintering process, the combination of Prussian blue and alumina can increase the porosity of the ceramic membrane, significantly improving its membrane flux compared to traditional alumina membranes.
[0015] 3. Compared with the impregnation loading method, in addition to the membrane surface, catalytic active sites are still distributed inside the membrane, which has a higher catalytic efficiency and thus exhibits a higher catalytic activity. The catalyst of the in-situ sintered membrane is not easy to lose, and the in-situ catalytic degradation of pollutants can be achieved during the filtration process, and the service life of the membrane is relatively longer.
[0016] 4. The co-sintering process of Prussian blue and alumina can effectively reduce the sintering temperature of alumina, so that it can be successfully sintered within 1000°C, thereby reducing the sintering cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a process flow chart for preparing catalytic ceramic membranes.
[0018] Figure 2 This is the SEM image of the catalytic ceramic membrane.
[0019] Figure 3 The catalytic performance of catalytic ceramic membrane in peroxymonosulfate solution. DETAILED DESCRIPTION
[0020] In order to make the objectives, technical solutions and advantages of the present invention more clear, the embodiments of the present invention are further described in detail below with reference to the accompanying drawings.
[0021] As attached Figure 1 As shown, the catalytic ceramic membrane prepared by the present invention is prepared by a dry pressing and sintering method, and the specific process is: Prussian blue-like powder and alumina are mixed in proportion, dry-pressed and formed, and then prepared by high-temperature calcination in a muffle furnace. The calcination temperature is 950°C, the insulation time is 6h, and the heating rate is 5°C / min.
[0022] The alumina is boehmite, with the molecular formula of γ-AlOOH (hydrated alumina), and comes from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0023] The Prussian blue-like powder is prepared in the laboratory. The specific preparation method is: weigh 1.85g potassium ferrocyanide powder and 2g cobalt chloride powder and dissolve them in 100ml water, stir continuously for 24 hours at room temperature, then centrifuge, then dry in a vacuum environment at 60°C, and finally crush with a mortar to obtain a Prussian blue-like powder (PBA).
[0024] The potassium ferrocyanide was purchased from Hubei Yunmei Technology Co., Ltd.
[0025] The cobalt chloride was purchased from Shanghai Jizhi Biochemical Technology Co., Ltd.
[0026] The biaxial bending strength (BFS) and compressive strength (CS) tests are used to comprehensively judge the brittleness, toughness and overall strength of the prepared catalytic ceramic membrane. A higher BFS means that the ceramic membrane can withstand greater external bending without breaking easily, while the CS test can reflect the ability of the ceramic membrane to withstand pressure in actual applications. Embodiment 1
[0027] 0.4g of Prussian blue powder and 1.6g of aluminum oxide were mixed evenly, and the addition ratio of the two substances was 1:4, wherein the particle size of the Prussian blue powder and the aluminum oxide was 100-200nm, and then the mixture was pressed for 5 minutes using a 30mm diameter mold and a hydraulic press at a pressure of 18 kPa to obtain a dry blank of the membrane, and its thickness range was 3mm. Then, in an air atmosphere, a muffle furnace was used for high temperature sintering at a temperature of 950°C for 6 hours, and the heating rate during sintering was 5°C per minute. Embodiment 2
[0028] The difference between this embodiment and the first embodiment is that 0.5 g of Prussian blue-like powder and 1.5 g of aluminum oxide are mixed evenly, and other operations are the same as those of the first embodiment. Embodiment 3
[0029] The difference between this embodiment and the first embodiment is that the sintering temperature of the muffle furnace is 1100° C., and other operations are the same as those of the first embodiment.
[0030] Comparative Example 1 When the film forming conditions are the same as those in Example 1, the sintering conditions are changed to firing in a tubular furnace under an argon atmosphere, and the other firing conditions are also the same as those in Example 1.
[0031] Comparative Example 2 No Prussian blue-like powder was added, and only 2.0 g of alumina was weighed for sintering. To ensure successful sintering of the membrane, the sintering temperature was 1400° C. The other membrane making conditions and sintering conditions were the same as those in Example 1.
[0032] The ceramic membranes prepared in the above examples and comparative examples were tested for biaxial flexural strength (BFS) and compressive strength (CS) (results are shown in Table 1), wherein the BFS and CS of the membrane prepared in Example 1 were 18 MPa and 46.5 MPa, respectively. According to the GB / T4100-2006 standard (I>30 MPa), the compressive strength was significantly higher, belonging to the first-class building material. Therefore, the ceramic membrane prepared in Example 1 can withstand high-pressure filtration well. In Example 2, alumina is the main matrix material in the ceramic membrane, and the high amount of Prussian blue added leads to a reduction in the content of alumina, which greatly reduces the strength of the fired membrane. Due to the addition of too much Prussian blue, the microstructure of the ceramic membrane will change unevenly, and its internal defects will increase, thereby reducing its BFS and CS, and the membrane is prone to brittle fracture. In Example 3, due to the increase in temperature, a more sufficient reaction between alumina and Prussian blue is promoted, thereby increasing the density of the ceramic membrane, reducing the pores, and making the microstructure of the membrane more uniform and dense. In summary, higher sintering temperatures help reduce porosity and defects and improve the overall mechanical properties of ceramic membranes. In Comparative Example 1, due to the oxidation of Prussian blue, the ceramic membrane will form an iron oxide phase, increase porosity and defects, reduce the density of the membrane, and thus reduce the BFS and CS of the membrane. However, for membranes using only alumina, no oxidation reaction will occur during sintering, and the densification process of alumina is usually smoother, which can form a uniform microstructure, reduce porosity, and thus enhance the mechanical properties of the material.
[0033] Table 1 Membrane strength properties Examples Biaxial bending strength (MPa) Compressive strength (MPa) Embodiment 1 18.0 46.5 Embodiment 2 9.8 24.3 Embodiment 3 29.8 55.3 Comparative Example 1 51.3 62.9 Comparative Example 2 70.5 90.7
[0034] Conventional alumina ceramic membranes are usually sintered at temperatures above 1100°C. Experiments have shown that the co-sintering of Prussian blue and alumina can effectively reduce the sintering temperature of alumina. At lower calcination temperatures, Prussian blue can maintain a relatively complete structure, and metal ions (such as Fe3+ or Co 3+ ) may retain a relatively stable oxidation state. At this time, the catalytic performance of Prussian blue is relatively excellent. It can better activate PMS to generate highly catalytic free radicals (such as SO4 •- ), thereby improving the catalytic efficiency. However, higher sintering temperatures may cause the Prussian blue-like crystal structure to be destroyed or reconstructed. Secondly, high temperatures may cause metal ions to migrate or aggregate, and may even lead to the formation of certain metal oxides (such as Fe2O3, Fe3O4, etc.). These changes may reduce the activation ability of the catalytic ceramic membrane to oxidants such as PMS, resulting in a decrease in its catalytic effect.
[0035] In summary, the catalytic ceramic membranes of Example 1, Comparative Example 1 and Comparative Example 2 were selected for SEM detection, and the results are as follows: Figure 2 As shown, it can be observed that the catalytic ceramic membrane of Example 1 has more small pores, and the porous structure is more evenly distributed on the membrane surface.
[0036] Water permeability is one of the basic properties of ceramic membranes. High water permeability can reduce the actual use pressure of ceramic membranes and save operating costs. The present invention uses a peristaltic pump and a microbial reactor to conduct a filtration experiment. The prepared ceramic membrane is fixed inside the microbial reactor and filtered using a peristaltic pump, wherein the flow rate of the peristaltic pump is 62.5L / m 2 ·h, and the hydraulic retention time of the membrane is 20s. The water permeability of Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2 were tested respectively, and the test results are shown in the following table.
[0037] Table 2 Membrane water permeability Examples Water permeability LMH / kPa Embodiment 1 6.7 Embodiment 2 6.9 Embodiment 3 5.5 Comparative Example 1 6.1 Comparative Example 2 4.1
[0038] It can be seen that the water permeability of Comparative Example 1 is improved by 49% compared with Comparative Example 2, while that of Example 1 is improved by 63% compared with Comparative Example 2, that is, when calcined in air, PBA is more conducive to the formation of the porous structure of the membrane, and the permeability can be increased to 1.63 times that of the alumina membrane. In addition, the Prussian blue-like composition of Example 2 accounts for 25%. Although the water permeability of the prepared catalytic ceramic membrane is also improved with the increase of the Prussian blue-like composition, Example 2 is not the best choice in terms of economic benefits. The water permeability of the catalytic ceramic membrane sintered at 1100°C in Example 3 is reduced by 18% compared with that of Example 1, because the lower calcination temperature helps to maintain the structural integrity of the Prussian blue-like composition, making its porosity higher, thereby maintaining a higher water permeability. However, higher temperatures may cause a certain degree of reconstruction of the crystal structure of the Prussian blue-like composition or promote the generation of aggregation, making the Prussian blue-like composition lattice more compact, and the pores may be reduced, thereby reducing the water permeability. The economic efficiency and water permeability are comprehensively determined to prepare the catalytic ceramic membrane under the conditions required by Example 1.
[0039] The membrane has the dual functions of separation and catalysis. It can be applied to the reaction to form a membrane-catalyzed reaction process that integrates catalysis and separation. The main principle is that while the reactants are being generated, they partially or completely pass through the membrane and leave the reaction zone. At the same time, the reactants remain in the reaction zone due to the selective permeability of the catalytic ceramic membrane, so that the chemical equilibrium continuously moves toward the product. Therefore, the present invention conducted a catalytic performance test on the catalytic ceramic membranes of Example 1 and Comparative Examples 1 and 2 using anionic dyes (AB9, edible brilliant blue solution). The catalytic test was carried out in a peroxymonosulfate solution (PMS), in which the AB9 concentration was 10 mg / L and the PMS concentration was 0.5 mM. The test results are as follows. Figure 3 As shown in the figure, it can be seen that the catalytic efficiency of the catalytic ceramic membrane of Example 1 is maintained at about 95% from 10min to 160min, while that of the catalytic ceramic membrane of Comparative Example 1 is only about 65%, and Comparative Example 2 has almost no catalytic effect. The low catalytic effect of Comparative Example 1 may be because the metal in the Prussian blue is prone to oxidation reaction when calcined in air, which may lead to an increase in the oxidation state of the metal (such as Fe 2+ Convert to Fe 3+ ), thereby enhancing its catalytic oxidation ability and effectively activating PMS. On the contrary, argon is an inert gas, and Prussian blue calcined in argon is not easy to oxidize metals, and the oxidation state of the metal may remain at a low state. In this case, the catalytic activity of the catalytic ceramic membrane is relatively low because the metal ions with low oxidation states (such as Fe 2+ ) is usually weak in its ability to activate PMS. In summary, it can be proved that the catalytic ceramic membrane sintered in air, that is, Example 1, can be well combined with PMS to degrade organic pollutants in situ on the surface of the ceramic membrane.
[0040] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a high-throughput and high-efficiency catalytic ceramic membrane, characterized in that: The steps include: (1) mixing a Prussian blue-like powder and an aluminum oxide powder in a certain proportion to obtain a mixture, and preparing a dry blank by dry pressing the mixture; (2) Sintering the dried blank at high temperature for 5.5 to 6.5 hours in an air atmosphere to obtain the high-throughput and high-efficiency catalytic ceramic membrane.
2. The method for preparing a high-throughput and high-efficiency catalytic ceramic membrane according to claim 1, characterized in that: The mass ratio of the Prussian blue-like powder to the aluminum oxide powder in step (1) is 1:3-5.
3. The method for preparing a high-throughput and high-efficiency catalytic ceramic membrane according to claim 1, characterized in that: The Prussian blue-like substance described in step (1) is prepared by the following method: 1.2-3 g of Prussian blue powder and 1.5-2.5 g of cobalt chloride powder are dissolved in 50-200 ml of water at 25° C., stirred continuously for 24 hours, and centrifuged and dried to obtain the Prussian blue-like substance.
4. The method for preparing a high-throughput and high-efficiency catalytic ceramic membrane according to claim 1, characterized in that: The specific method of preparing the dry blank by the dry pressing method described in step (1) is as follows: pressing the mixture at a pressure of 10 to 30 kPa for 3 to 7 minutes to obtain a dry blank of the membrane.
5. The method for preparing a high-flux and high-efficiency catalytic ceramic membrane according to claim 3, characterized in that: The thickness of the dry blank is 2-4 mm.
6. The method for preparing a high-flux and high-efficiency catalytic ceramic membrane according to claim 1, characterized in that: The high temperature sintering temperature is 950-1100°C.
7. A high-throughput and high-efficiency catalytic ceramic membrane prepared by the method according to any one of claims 1 to 6.
8. Use of the high-throughput and high-efficiency catalytic ceramic membrane according to claim 7 in water treatment.
9. The use according to claim 8, characterized in that: The high-flux and high-efficiency catalytic ceramic membrane is used for peroxymonosulfate activation and oxidation of organic pollutants.
Citation Information
Patent Citations
Diatomite substrate-shaped ceramic membrane, and preparation method and application thereof
CN103011893A
Efficient organic-pollution-resistant scale-inhibiting ceramic membrane and preparation and in-situ regeneration method thereof
CN113663526A
Sodium-ion battery positive electrode material and preparation method thereof
CN116072834A
Preparation method of Prussian blue-like inorganic fine separation membrane based on interface confinement principle
CN117123060A
Preparation method and application of cobalt-doped functional ceramic membrane
CN117771959A